Characterizing fish responses to a river restoration over 21 years based on species' traits. Issue 5 (4th July 2017) - Höckendorff, Stefanie; Tonkin, Jonathan D.; Haase, Peter; Bunzel‐Drüke, Margret; Zimball, Olaf; Scharf, Matthias; Stoll, Stefan
Abstract: Understanding restoration effectiveness is often impaired by a lack of high‐quality, long‐term monitoring data and, to date, few researchers have used species' trait information to gain insight into the processes that drive the reaction of fish communities to restoration. We examined fish‐community responses with a highly resolved data set from 21 consecutive years of electrofishing (4 years prerestoration and 17 years postrestoration) at multiple restored and unrestored reaches from a river restoration project on the Lippe River, Germany. Fish abundance peaked in the third year after the restoration; abundance was 6 times higher than before the restoration. After 5–7 years, species richness and abundance stabilized at 2 and 3.5 times higher levels relative to the prerestoration level, respectively. However, interannual variability of species richness and abundance remained considerable, illustrating the challenge of reliably assessing restoration outcomes based on data from individual samplings, especially in the first years following restoration. Life‐history and reproduction‐related traits best explained differences in species' responses to restoration. Opportunistic short‐lived species with early female maturity and multiple spawning runs per year exhibited the strongest increase in abundance, which reflected their ability to rapidly colonize new habitats. These often small‐bodied and fusiform fishes typically live in dynamic and ephemeral instream and floodplain areas that river‐habitat restorations often aim to create, and in this case their increases in abundance indicated successful restoration. Our results suggest that a greater consideration of species' traits may enhance the causal understanding of community processes and the coupling of restoration to functional ecology. Trait‐based assessments of restoration outcomes would furthermore allow for easier transfer of knowledge across biogeographic borders than studies based on taxonomy.